Is There A Stable Long-run Relationship Between Unemployment And Productivity? - Jalles, João Tovar (Comparative Economic Research. Central and Eastern Europe, 2015)
This paper assesses whether productivity and unemployment have a stable long-run relationship. We explore a panel of 19 OECD countries between 1970 and 2012 and rely on recently developed time series econometric methods. Our findings suggest that unemployment and productivity are non-stationary in levels and in many individual cases these series are cointegrated, even after accounting for possible structural breaks. For many individual countries the long-run effect seems to be generally positive. There is also evidence of two-way causality, but the stronger directional relationship runs from unemployment to productivity.